Propuesta de un plan estratégico para la ferretería “San Antonio” de la ciudad de Zumbi cantón Centinela del Cóndor de la provincia de Zamora Chinchipe - Quezada Torres, Jenny Ricarda (2017)
The present investigation refers to a strategic plan designed for the "San Antonio" hardware company, located in the city of Zumbi in the Canton Centinela del Cóndor, belonging to the province of Zamora Chinchipe, which covers the level of difficulty that the company has , Since in spite of the years of institutional life it has not been able to obtain favorable results that benefit it; Which is mainly attributed to the fact that the objectives that were first raised have not yet been reached at one hundred percent, since the lack of strategies hinders its achievement. In this context, the elaboration and implementation of a strategic plan aims to improve the organizational structure in which there is participation of all those who are part of the company "San Antonio" In the development of this research work, some of the research methods were used, for example: deductive, inductive, descriptive and statistical method; Techniques such as observation, which allowed us to know the current situation of the company; The interview that was directed to the manager of the company and the surveys applied to 8 internal clients, as well as 282 external clients. The following results were determined from the study: the internal analysis (EFI matrix) obtained a weighted total percentage of 2.08%, which shows that weaknesses prevail over the strengths. The EFE matrix, for its part, shows the following: with a weighted total of 2.87%, a value that is above the midpoint (2.5), indicating that it has the possibility of taking advantage of the opportunities that exist in the external environment In which it develops to control its threats. With the aforementioned results, the high impact matrix was carried out to be able to carry out the combination of strategies, considering aspects such as: FO, FA, DO, DA, that allowed to conclude with the present work facilitating the development of the objectives The proposed plan. Finally, it is concluded and recommends that the administrative management of the company must use modern management techniques, which guarantee the best functioning of the activities within the company, and that allow the fulfillment of the objectives.